2011
DOI: 10.1007/s11249-011-9894-3
|View full text |Cite
|
Sign up to set email alerts
|

1D Model of Precursors to Frictional Stick-Slip Motion Allowing for Robust Comparison with Experiments

Abstract: In this article, we study the dynamic behaviour of 1D spring-block models of friction when the external loading is applied from a side, and not on all blocks like in the classical Burridge-Knopoff-like models. Such a change in the loading yields specific difficulties, both from numerical and physical viewpoints. To address some of these difficulties and clarify the precise role of a series of model parameters, we start with the minimalistic model by Maegawa et al. (Tribol. Lett. 38: 313, 2010) which was prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
82
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 38 publications
6
82
1
Order By: Relevance
“…Generally, each slip event propagates further than the previous rupture, until they reach the leading edge, which is considered to be global sliding. Numerical simulations using mass-spring models (1D (Maegawa et al, 2010;Amundsen et al, 2012) and 2D (Trømborg et al, 2011)) reproduced qualitatively this behavior and show the http://dx.doi.org/10.1016/j.mechmat.2014.03.009 0167-6636/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Generally, each slip event propagates further than the previous rupture, until they reach the leading edge, which is considered to be global sliding. Numerical simulations using mass-spring models (1D (Maegawa et al, 2010;Amundsen et al, 2012) and 2D (Trømborg et al, 2011)) reproduced qualitatively this behavior and show the http://dx.doi.org/10.1016/j.mechmat.2014.03.009 0167-6636/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 68%
“…Ruptures at bimaterial interfaces are known for their richness of complex mechanics (Coker et al, 2003;Lykotrafitis and Rosakis, 2006) and to date no experiments of similar material interfaces have been conducted to compare with the bimaterial system of Rubinstein et al (2007). In all numerical studies of the transition from sticking to sliding, this bi-material effect has been approximated by a deformable-rigid interface (Maegawa et al, 2010;Amundsen et al, 2012;Trømborg et al, 2011;Kammer et al, 2012;Bar-Sinai et al, 2013;Otsuki and Matsukawa, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the past ten years, several experimental groups developed new optical methods to obtain spatially resolved mechanical measurements [4,5,6,7,8], which triggered intense subsequent theoretical and numerical investigations [9,10,11,12,13,14,15]. Fineberg and collaborators studied the onset of sliding of a multi-contact interface, in a planeplane contact configuration, submitted to an adiabatic tangential loading [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…While we have not yet studied our model in either 2D or 3D systems, previous investigations of edge-driven extended elastic sliders [23][24][25] demonstrated that 1D consideration provides a good description of friction in 3D system. Thus, we expect that qualitative conclusions of this work will hold also for 3D systems, in particular for graphene layers deposited on substrates [26] and clusters studied in the context of nanomanipulation [27].…”
mentioning
confidence: 99%